Uji Senyawa Inhibitor Amilase dari Tempuyung (Sonchus arvensis) sebagai Anti Diabetes Secara In Silico - Amal, Ilham Ikhlasul; Hayati, Asya Nur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Global phenomena such as global warming and climate change have broad impacts, including the rapid development of invasive species that disrupt the balance of the ecosystem. One of the invasive species is Tempuyung (Sonchus arvensis). Although known as a weed, this plant has the potential as an anti-diabetic agent. This study aims to identify bioactive compounds in Sonchus arvensis that can inhibit the amylase enzyme in silico. The methods used include collecting data on the structure of the amylase enzyme and bioactive compounds, docking with PyRx, and residue analysis using BIOVIA Discovery Studio. The results showed that the Rhamnetin compound had the best binding affinity value (-8.6 kcal/mol), ideal RMSD (<2.0 Å), and the highest percentage of Binding Site Similarity (BSS) (100%). In addition, Luteolin-7-O-Glucoside also showed high inhibition potential. The conclusion of this study is that Rhamnetin and Luteolin-7-O-Glucoside in Sonchus arvensis have the ability to inhibit the amylase enzyme, making it a potential candidate as an anti-diabetic agent.